Cefepime plasma concentrations and clinical toxicity: a retrospective cohort study. (July 2017) - Huwyler, T.; Lenggenhager, L.; Abbas, M.; Ing Lorenzini, K.; Hughes, S.; Huttner, B.; Karmime, A.; Uçkay, I.; von Dach, E.; Lescuyer, P.; Harbarth, S.; Huttner, A.
Abstract: Objectives: Cefepime remains an important antibiotic for severe bacterial infections, yet some meta-analyses have shown elevated mortality among patients randomized to it. Therapeutic drug monitoring (TDM) of β-lactam antibiotics is increasing, but optimal plasma concentrations remain unknown. We examined clinical outcomes of patients undergoing cefepime TDM in an initial effort to define the drug's toxicity threshold. Methods: In this single-centre retrospective cohort study, we enrolled all adult hospitalized patients receiving cefepime and undergoing TDM from January 2013 through July 2016. The primary outcome was the incidence of clinical toxicity; a secondary outcome was clinical failure. Plasma samples were analysed via high-performance liquid chromatography with ultraviolet detection. Results: A total of 161 cefepime concentrations were drawn from 93 patients. Roughly half (82/161, 51%) and one-third (49/161, 30%) were trough and steady-state levels from patients receiving intermittent and continuous infusions, respectively; median concentrations were 17.6 mg/L (IQR 9.7-35.2) and 29.2 mg/L (IQR 18.9-45.9). Ten patients (11%) experienced a neurologic event considered at least possibly related to cefepime; neurotoxicity was associated with poorer renal function (median creatinine clearance 54 (IQR 39-97) vs. 75 mL/min/1.73 2 (IQR 44-104)) and longer cefepime durations (mean 8.3 (SD ± 6.7) vs. 13.3 days (± 14.2), p = 0.071). Patients with trough levels >20 mg/L had a fivefold higher risk for neurologic events (OR 5.05, 95% CI 1.3-19.8). Conclusions: Neurotoxicity potentially related to cefepime occurred at plasma concentrations >35 mg/L. For those receiving intermittent infusions, trough concentrations >20 mg/L should be avoided until further information is available from prospective studies.